Cundinamarca gives you to participatory budgets (2017)
This document presents a historical overview of the application and development of participatory budgets in Latin America and Colombia, reviewing successful experiences in the adoption of this model of citizen participation. Subsequently, a model proposal for the application of participatory budgets for the Department of Cundinamarca is carried out, which analyzes the situation and phases in which PPs must be implemented during the 2017 period, with the participation and integration of the “Juntas de Acción Comunal” that play a principal role in the territorial entities of the Department.